Invisible hands behind the corporate governance practices in Malaysia : a literature review - Htay, Sheila Nu Nu (2012)
The issues of corporate governance became very popular in the corporate world in UK, USA and Europe during the last two decades. With the opening up of economies and liberalization, the concern for corporate governance also spread to the developing world. Therefore, most of the developed and developing countries, including Malaysia have laid down corporate governance guidelines to enhance the current governance practices. Based on the analysis of the contents in the corporate governance codes, most of the recommendations are founded on the concept of agency theory. Unfortunately, the majority of the findings of researchers show that the results are not in line with the theoretical expectations. In Malaysia, Malaysian Code on Corporate Governance was introduced in 1998 and eventually; it has been amended in 2000 and 2007. However, some of the findings on corporate governance in Malaysia are not in line with the recommendations of the Code. Thus, this study examines the possible reasons that hinder current corporate governance system less effective in Malaysia. The main reasons for this problem are due to nature of ownership structure, political and culture background of Malaysia and the adoption of unsuitable foreign corporate governance template. The findings of this research will be useful for the regulators to develop future rules and regulations and implement them accordingly.